2019
DOI: 10.32098/mltj.04.2015.07
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of corticosteroid effect in plantar fasciitis: additional utility of ultrasound

Abstract: Background: although plantar fascia thickening is well documented as a sonographic criterion for the diagnosis of plantar fasciitis (PF), however it was less evaluated as an objective measure of response to treatment. It is unknown to what extent if any different responses to different treatments are related to the ultrasound (US) morphology changes. We aimed to evaluate changes in US findings in correlation to pain reported. Methods: this prospective observational trial included 21 plantar fasciitis patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Musculoskeletal ultrasonography is an effective technique to visualize normal and pathological tendons and to non-invasively evaluate (qualitative assessment) 1,2 or measure (quantitative analysis) parameters reflecting tendon size (length, thickness, and cross-sectional area) and structure (echo-intensity) [3][4][5][6] . Patellar tendon ultrasonography is commonly performed in the routine management of athletes of different disciplines to investigate tendon abnormalities that may occur due to repetitive tendon overload [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal ultrasonography is an effective technique to visualize normal and pathological tendons and to non-invasively evaluate (qualitative assessment) 1,2 or measure (quantitative analysis) parameters reflecting tendon size (length, thickness, and cross-sectional area) and structure (echo-intensity) [3][4][5][6] . Patellar tendon ultrasonography is commonly performed in the routine management of athletes of different disciplines to investigate tendon abnormalities that may occur due to repetitive tendon overload [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Up to our knowledge, no studies have examined the change in echogenicity in PF after the treatment with ESWT or LLLT yet. However, Moustafa et al (18) showed statistically significant reduction in number of hypoechoic feet after dexamethasone injection in patients with PF (p <0.05) (18) . Even though the present study supports the short-term effectiveness of ESWT and LLLT in the management of PF with a better improvement in pain in LLLT group, these findings should be interpreted in the light of some limitations.…”
Section: Discussionmentioning
confidence: 96%
“…Images obtained just medial to the midline at proximal end of plantar fascia distal to its origin from the medial tubercle of calcaneus. Thickness of the plantar fascia is measured at the thickest portion from the base of the medial calcaneal tubercle where a bright echogenic line was easily visible (18) . A perpendicular measurement was then taken to the top of the plantar fascia image where the most inferior border of the plantar fascia was discernable from fat.…”
Section: Methodsmentioning
confidence: 99%
“…Plantar fasciopathy is one of the main causes of heel pain in adults, with approximately 10% of the population suffering from this condition at some point of their lives. 13 Pain and stiffness in the heel, especially at the first steps in the morning, are common in patients with plantar fasciopathy, and can negatively impact activities of daily living. 4 Patients generally report poor quality of life because heel pain prevents them from performing basic activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…4 Patients generally report poor quality of life because heel pain prevents them from performing basic activities of daily living. 2,5…”
Section: Introductionmentioning
confidence: 99%